Evaluating the efficacy of using a novel gaze-based attentive user interface to extend ADHD children's attention span. Issue 169 (January 2023) - Shen, Haifeng; Asiry, Othman; Babar, M. Ali; Bednarz, Tomasz
Highlights: first of its kind that integrates multiple color schemes through a novel gazebased attentive user interface specifically for ADHD children who have difficulties in maintaining focus while reading to extend their attention span combination of questionnaire-based subjective method and an eye-tracking based objective method to enhance and strengthen the study validity insights gained from this research in understanding the effect of changing color schemes on the attention process could be used in developing more applications for children with special education needs in general and, in particular, children with ADHD Abstract: Attention Deficit Hyperactivity Disorder (ADHD) is a neurobiological condition that often affects school children. A major symptom is short attention span, which may negatively influence their academic performance, specifically in those tasks that require concentration. Extending the attention span for those children could help them do better in school and in life. In this work, we propose a novel gaze-based visual attentive interface designed with the three common text color schemes of highlighting, contrast, and sharpening/blurring for the purpose of extending ADHD children's attention span in performing reading tasks. This design is based on the optimal stimulation theory stating that children with attention and hyperactivity disorders seek the optimum stimulation and attend to the task presenting extra stimulation. Children's attention state is monitored by a webcam for eye tracking, while mouse tracking was used as the second modality for gaze prediction because some children had difficulties in maintaining the calibration of webcam. Visual color schemes are applied to evaluate different ways of maintaining attention in the process of reading. This study aims to evaluate the efficacy of such a novel interface with two fixation-based metrics – the number of read words and the total time spent in reading text – to measure attention span. The results show that these children performed better in the presence of any color scheme in comparison with using no color, with highlighting the most effective, followed by contrast and then sharpening/blurring. These findings are independent of the tracking modalities and confirm the viability of using a gaze-based attentive user interface designed with adaptive color schemes to extend ADHD children's attention span.